2019
DOI: 10.1017/jea.2019.26
|View full text |Cite
|
Sign up to set email alerts
|

Natural Disasters and Political Participation: The Case of Japan and the 2011 Triple Disaster

Abstract: What effect do natural disasters have on political participation? Some argue that natural disasters decrease political participation because of the way they reduce individual and group resources. Others argue that they stimulate political participation by creating new social norms. Previous studies have been limited both by their focus on a specific disaster type and a lack of regional variation. This article advances the literature by assessing the effect of the 2011 triple disaster in Japan on political part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…For example, wildfire exposure has a stronger effect on climate attitudes among respondents who believe in the scientific consensus around climate change (Lacroix, Gifford, and Rush 2019). Alternatively, climate-related political behaviors may be overshadowed by other factors that influence political preferences during crises, including public evaluation of government performance (Bechtel and Hainmueller 2011;Malhotra and Kuo 2008) and political participation (Jenkins 2019). All the same, empirically many members of the public have linked wildfires to climate change (Brenkert-Smith, Meldrum, and Champ 2015), with a recent survey showing 69% of Californians believe that climate change is making wildfires worse.…”
mentioning
confidence: 99%
“…For example, wildfire exposure has a stronger effect on climate attitudes among respondents who believe in the scientific consensus around climate change (Lacroix, Gifford, and Rush 2019). Alternatively, climate-related political behaviors may be overshadowed by other factors that influence political preferences during crises, including public evaluation of government performance (Bechtel and Hainmueller 2011;Malhotra and Kuo 2008) and political participation (Jenkins 2019). All the same, empirically many members of the public have linked wildfires to climate change (Brenkert-Smith, Meldrum, and Champ 2015), with a recent survey showing 69% of Californians believe that climate change is making wildfires worse.…”
mentioning
confidence: 99%
“…While some studies have found that natural disasters have a positive effect on political participation (Aldrich 2012;Chen 2013;Fair et al 2017;Jenkins 2019), others have found a negative effect (Sinclair, Hall, and Alvarez 2011;Rudolph and Kuhn 2018;Marsh 2022) and yet others have found no effect (Bodet, Thomas, and Tessier 2016).…”
Section: Natural Disasters and Political Participationmentioning
confidence: 99%
“…In an influential study, (Blattman 2009) found that those affected by the violent conflict in Uganda (to the extent that they were abducted) had a higher propensity to participate in politics. It has also been argued that the mechanism of post-traumatic growth could explain the increased voter turnout in postdisaster elections (Fair et al 2017;Jenkins 2019). The argument that can be derived from the theory of post-traumatic growth is therefore that individuals who experience trauma following a natural disaster (which, as demonstrated above, are highly political events) also are more likely to participate in politics, because of increased personal strength and subsequent increased internal political efficacy.…”
Section: Natural Disasters and Political Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some notable exceptions, which provide mixed results. While some studies indicate that extreme weather events did not affect turnout (Bodet, Thomas, and Tessier, 2016; Lasala‐Blanco, Shapiro, and Rivera‐Burgos, 2017), others report negative (Rudolph and Kuhn, 2018; Zelin and Smith, 2023) or positive (Fair et al, 2017; Jenkins, 2019) effects on electoral participation. The most sophisticated study to date, by Sinclair, Hall, and Alvarez (2011), concludes that in the aftermath of Hurricane Katrina (2005), turnout decreased on average but increased in the most affected areas.…”
Section: Introductionmentioning
confidence: 99%